2009
DOI: 10.1177/0363546509332817
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Analysis of the Iliopsoas Tendon and Its Relationship to the Acetabular Labrum

Abstract: Knowledge of the cross-sectional anatomy of the iliopsoas tendon and its relationship to the acetabular labrum will better assist surgeons in treating lesions associated with iliopsoas injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 13 publications
3
74
1
Order By: Relevance
“…For patients with signs and symptoms of concomitant internal snapping hip syndrome or psoas impingement syndrome [2,3,27,30,33], we performed separate diagnostic injections in the area of the iliopsoas bursa and a positive diagnosis applied to those with immediate considerable to complete relief of symptoms from the injection [1]. Chondral and labral disorders were evaluated using high-resolution, noncontrast MRI based on evidence from our institution regarding the equivalence or superiority to MR arthrograms for evaluation of labral disorders [50,60] ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For patients with signs and symptoms of concomitant internal snapping hip syndrome or psoas impingement syndrome [2,3,27,30,33], we performed separate diagnostic injections in the area of the iliopsoas bursa and a positive diagnosis applied to those with immediate considerable to complete relief of symptoms from the injection [1]. Chondral and labral disorders were evaluated using high-resolution, noncontrast MRI based on evidence from our institution regarding the equivalence or superiority to MR arthrograms for evaluation of labral disorders [50,60] ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is in this very region that a thickened and inflamed psoas tendon can be found in cases involving internal snapping hip or hip dysplasia. 23,24 In a healthy hip, anterior capsular contributions to stability and anterior restraint are less important, and this explains the relative ease of anterior capsular resection in exposing the psoas tendon during capsular release and psoas takedown for psoas impingement. 23,24 Conversely, in the dysplastic hip, the anterior capsule and pericapsular structures 4 play a greater role in providing anterior restraint and are often thickened and hyperemic, making anterior release more difficult.…”
Section: Capsular Thicknessmentioning
confidence: 99%
“…However, in patients with iliopsoas impingement there is mechanical conflict between the iliopsoas muscle and the labrum, resulting in distinct labral lesions directly anteriorly (3 and 9-o'clock for right and left hips, respectively). It has been shown that the iliopsoas tendon directly overlies the anterior capsulolabral complex at the three-o'clock position for right hips using fresh-frozen cadavers [34]. Another study examining the findings of MR arthrograms has confirmed this finding [35].…”
Section: Iliopsoas Impingement Anatomical Considerationsmentioning
confidence: 89%